Emerging tendency towards autoimmune process in major depressive patients: A novel insight from Th17 cells - Chen, Yili; Jiang, Tang; Chen, Peisong; Ouyang, Juan; Xu, Guiyun; Zeng, Zhijie; Sun, Yanhong (Psychiatry research, 2011)
Evidence indicates that there is an emerging tendency towards autoimmunity occuring in major depressive disorder (MDD). The aim of our study is to investigate the mechanism of autoimmune process in MDD from a novel insight of Th17 cells, which have been identified as the significant activators of autoimmunity. We included 40 patients with MDD and 30 healthy control subjects. An indirect immunofluorescence test was used for the detection of serum antinuclear antibodies (ANA), and revealed that the patient group was positive more frequently than the control group. By flow cytometric analysis, depressed subjects revealed a significant increase in peripheral Th17 cell number, and an obvious decrease in T-reg cell number, showing an imbalance of Th17/Treg ratio compared to healthy controls. We also found a higher level of RORγt (retinoic acid-related orphan receptor-γt, the specific transcription factor of Th17 cell) mRNA expression in peripheral blood lymphocytes by RT-PCR and serum concentration of IL-17 by ELISA in patients. In conclusion, our study showed a potential role of Th17 cells in the autoimmune process in MDD patients, thus contributing to the existing evidence of autoimmune inclination in MDD.